Anxiety and distress during COVID-19 in university students - Salvado, Ana Catarina Mendonça (2022)
International studies have shown the consequences of the covid-19 pandemic in increasing anxiety and distress. Since technologies were used more during the pandemic, especially by younger people, namely, to obtain health information, it is relevant to study the relationship between anxiety, distress and eHealth in students. The sample consisted of a total of 1390 university students, of both genders, ranging in age from 18 to 70 (M=23.94 years; SD=7.49), who responded to the online questionnaire during the pandemic, which included sociodemographic questions, the Kessler Psychological Distress Scale (K-10), the Coronavirus Anxiety Scale (CAS), and the eHealth Literacy Scale (eHEALS). Results showed that most students had high distress (K-10), adaptive anxiety (CAS), and good levels of eHealth (eHEALS). Significant correlations were found between anxiety and distress, and between distress and health satisfaction. In addition, differences emerged between the means of the sociodemographic groups for the distress, anxiety, and eHealth variables. This study additionally points out risk factors for developing higher levels of distress, anxiety, and better eHealth skills. Psychological interventions are needed to combat distress and anxiety in academic settings.